1997
DOI: 10.4049/jimmunol.159.9.4145
|View full text |Cite
|
Sign up to set email alerts
|

The PU.1 binding site is a cis-element that regulates pro-B/pre-B specificity of Vkappa-Jkappa joining.

Abstract: We have previously shown that the PU.1 binding motif (GAG GAA) in the 3'-enhancer region in the Ig kappa gene is responsible for the negative regulation of tissue (B/T)-specific Vkappa-Jkappa joining. Here we report that the PU.1 binding site also regulates the stage (pro-B/pre-B) specificity of Vkappa-Jkappa joining. In the substrate with base substitutions in the PU.1 binding motif, recombination took place in both pro-B (B220dull/CD43+) and pre-B (B220dull/CD43-) cells. In the transcriptional regulation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was demonstrated that EBF1 is necessary not only for the survival, proliferation, and signaling of pro-B cells and peripheral B-cell subsets (such as B1 cells and marginal zone B cells) but also for germinal center formation and class switch recombination (30). Ikaros and PU.1 contribute to lymphoid progenitor cell differentiation into pro-B cells, and this process is blocked when these two TFs are deficient (31)(32)(33)(34). The overexpression of EBF1 induces Ikaros-KO Lin-Sca1 hi c-Kit hi cells to differentiate into pro-B cells (35).…”
Section: Ebf1mentioning
confidence: 99%
“…It was demonstrated that EBF1 is necessary not only for the survival, proliferation, and signaling of pro-B cells and peripheral B-cell subsets (such as B1 cells and marginal zone B cells) but also for germinal center formation and class switch recombination (30). Ikaros and PU.1 contribute to lymphoid progenitor cell differentiation into pro-B cells, and this process is blocked when these two TFs are deficient (31)(32)(33)(34). The overexpression of EBF1 induces Ikaros-KO Lin-Sca1 hi c-Kit hi cells to differentiate into pro-B cells (35).…”
Section: Ebf1mentioning
confidence: 99%